Study The Synthesis Parameters And Effect Of Addition Of Acid Hydrolyzed Sago Starch On Mechanical Properties Of NR And XNBR Latex Films - Yap, Soon You (Universiti Sains Malaysia, 2018)
The objective of this research was to develop a small particle size sago starch with the motivation to improve mechanical properties and biodegradability of latex films upon disposal. The research’s stage 1 investigated the optimum synthesis parameter of the acid hydrolyzed sago starch (AHSS) powder. The native sago starch (NSS) were hydrolyzed with different hydrolysis condition at different temperature, acidity and duration. The results showed that the optimum synthesis parameters of preparation acid hydrolysis sago starch fillers (313.10 nm) was at 2.18 M sulphuric acid under non heated condition (27°C) for 7 days. Stage 2 of work, investigated the effect of addition of AHSS fillers on mechanical properties (tensile properties and tear strength), physical properties (crosslink density measurement), morphological (optical and scanning electron microscopes (SEM)) and biodegradability of NR latex films and XNBR latex films (mass loss analysis). It was found that the AHSS has improved mechanical properties and swelling resistance of latex films as compared to NSS filled NR latex films and NSS filled XNBR latex films. This was contributes by improvement in compatibility of sago starch particles with rubber matrix which attributed from the relative smaller particle size, presence of sulphate ester group and low crystallinity of AHSS. The biodegradation assessment by mass loss analysis indicates AHSS filled NR latex and XNBR filled latex films has higher degree of biodegradation rate. Morphological analyses with optical microscope shows the discoloration of the films and voids resulted from an increased of degradation sites for microorganisms during the biodegradation process. Overall, AHSS has increased the mechanical properties, physical properties and biodegradability of both type of latex films (NR and XNBR) compared to NSS.